Health-promoting activities among Saudi Arabian parents of children with disabilities: A cross-sectional study - Salmah A. Alghamdi; Muna I. Assiri; Reem A. Fallatah; Farah M. Albeladi; Hawa Alabdulaziz; Fatimah Alsaggaf (Belitung Nursing Journal)
Background: Engaging in health-promoting activities is crucial for maintaining overall well-being. However, parents of children with disabilities often face unique challenges that can impact their ability to engage in such activities. These challenges may include increased caregiving responsibilities, limited access to resources, and emotional and physical burdens, which may hinder their involvement in health-promoting behaviors.